Optical Myringotomy Knife - De Leon, Rozelle O.; Amable, Jay Pee M. (Philippine journal of otolaryngology head & neck surgery, 2017)
Objective: To describe an improvised optical myringotomy knife essential in creation of an incision in a myringotomy simulator. Methods: Study Design: Instrumental Innovation Setting:           Tertiary Private Hospital Subject:          None Results: The optical myringotomy knife was able to create incisions on mock membranes made up of polyethylene film (Cling Wrap) in a myringotomy simulator. The incisions measured approximately 2 mm with sharp edges indicating that the myringotomy knife was able to penetrate the mock membrane with ease. It provided good control in performing myringotomy incisions under endoscopic visualization of the tympanic membrane. Conclusion: Our initial experience with this optical myringotomy knife for tympanostomy tube insertion suggests that it may greatly improve the performance of myringotomy especially among less experienced surgeons. Further studies may establish its accuracy and replicability in vitro, after which formal in vivo trials can be attempted.